Evaluation of phenotypic tests for detection of Klebsiella pneumoniae carbapenemase and metallo-beta-lactamase in clinical isolates of Escherichia coli and Klebsiella species - Kalpana Chauhan; Anita Pandey; Ashish K Asthana; Molly Madan (Wolters Kluwer Medknow Publications, 2015)
Context: Carbapenemase production is an important mechanism responsible for carbapenem resistance. Aims: Phenotypic detection and differentiation of types of carbapenemase in carbapenem resistant Enterobacteriaceae is important for proper infection control and appropriate patient management. Settings and Design: We planned a study to determine the occurrence of Class A Klebsiella pneumoniae carbapenemase (KPC type) and Class B Metallo-β-lactamase (MBL type) carbapenemase in hospital and community. Materials and Methods: Clinical isolates of Escherichia coli and Klebsiella species and simultaneously evaluate different phenotypic methods for detection of carbapenemases. Results: It was observed that 20.72% clinical isolates of E. coli and Klebsiella spp. were resistant to carbapenem on screening of which, 14.64% were E. coli and 29.69% were Klebsiella spp. Using phenotypic confirmatory tests the occurrence of carbapenemase production was found to be 87.01% in E. coli and 91.51% in Klebsiella spp. using both modified Hodge test (MHT) and combined disk test (CDT) using imipenem-ethylenediaminetetraacetic acid. Conclusions: Both MBL and KPC type carbapenemases were seen among clinical isolates of E. coli and Klebsiella spp. CDT is simple, rapid and technically less demanding procedure, which can be used in all clinical laboratories. Supplementing MHT with CDT is reliable phenotypic tests to identify the class A and class B carbapenemase producers.